2017
DOI: 10.1186/s13046-017-0547-8
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-containing compound platinum pyrithione suppresses ovarian tumor proliferation through proteasome inhibition

Abstract: BackgroundOvarian carcinoma is one of the most aggressive gynecological malignant neoplasms and makes up 25–30% of all cancer cases of the female genital tract. Currently, resistance to traditional chemotherapy is a great challenge for patients with Epithelial ovarian cancer (EOC). Therefore, identifying novel agents for EOC treatment is essential and urgent.MethodMTS assay was used to analyze the cell viability and proliferation of cancer cells. Flow cytometry was employed to analyze cell cycle distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…This assay was performed as we previously reported [28]. Breast cancer cell was exposed to the indicated treatment and the total proteins were extracted using cell lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…This assay was performed as we previously reported [28]. Breast cancer cell was exposed to the indicated treatment and the total proteins were extracted using cell lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Platinum pyrithione (PtPT) and b-AP15 have been defined as 19 S DUBs inhibitors, targeting USP14 and UCHL5 12 , 13 without effect on the 20 S proteasome. Both b-AP15 and PtPT exert potent anti-cancer effects within a dose range that is biologically safe 13 15 . Our previous study also showed the anti-tumor potential of PtPT on Bcr–Abl-positive cell lines 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, most cases of non‐muscle‐invasive BC can be essentially cured when treated with a combination of surgical resection and chemotherapy at an early stage . Obviously, the key to improving BC patient prognosis is early diagnosis and treatment . However, traditional imaging techniques, such as ultrasonography, vesical radiography and magnetic resonance imaging, are of limited value for an early, definitive diagnosis of BC .…”
Section: Introductionmentioning
confidence: 99%